Patchy Pulsating Aurora and its Relationship to Cold Plasma in the Magnetospheric Equatorial Plane ... - Rae, Kyle (Graduate Studies, 2014)
Patchy pulsating aurora occur frequently after geomagnetic disturbances. These aurora consist of patches which are typically tens to one hundred or more kilometers in spatial extent. The patches sometimes pulsate (as their name suggests) quasi-periodically. The luminosity results from upper atmospheric atoms and molecules that have been excited by electrons that precipitate onto our atmosphere from above, however it is not known what process or processes lead to the formation of the patches, in particular their shape. In this thesis I investigate the origin of the shape of the patchy pulsating aurora. To accomplish this I have created a list of 53 instances of patchy pulsating aurora which I found using a network of all-sky cameras. For each event in this list I tracked the movement of and change in longitudinal extent of these auroral patches. As well, I used an empirical magnetic field model to map the patch shapes to the magnetic equatorial plane in the magnetosphere. I then assumed that the equatorial ...